2008
DOI: 10.1111/j.1365-2249.2008.03671.x
|View full text |Cite
|
Sign up to set email alerts
|

Depressed activation of the lectin pathway of complement in hereditary angioedema

Abstract: SummaryThe possibility of simultaneous measurement of the classical pathway (CP), mannan-binding lectin (MBL)-lectin pathway (LP) and alternative pathway (AP) of complement activation by the recently developed Wielisa method allowed us to investigate the in vivo significance of the C1-inhibitor (C1INH) in three complement activation pathways. Functional activity of the CP, LP and AP were measured in the sera of 68 adult patients with hereditary angioedema (HAE) and 64 healthy controls. In addition, the level o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 32 publications
0
9
0
2
Order By: Relevance
“…However, compared with healthy controls, the activity of the MBL pathway and MASP-2 were found to be similar or even lower in HAE patients. 45 , 46 It was explained that the lower MASP-2 levels were due to the consumption, and that the lectin pathway was still activated but depressed in HAE. 46 In one study, the concentrations of MASP-2 and ficolin-3/MASP-2 complex were increased during angioedema attacks compared with remission periods in the same HAE patient, 47 indicating that the lectin pathway was activated during attacks.…”
Section: Introductionmentioning
confidence: 99%
“…However, compared with healthy controls, the activity of the MBL pathway and MASP-2 were found to be similar or even lower in HAE patients. 45 , 46 It was explained that the lower MASP-2 levels were due to the consumption, and that the lectin pathway was still activated but depressed in HAE. 46 In one study, the concentrations of MASP-2 and ficolin-3/MASP-2 complex were increased during angioedema attacks compared with remission periods in the same HAE patient, 47 indicating that the lectin pathway was activated during attacks.…”
Section: Introductionmentioning
confidence: 99%
“…Also relevant to our analysis, becasue of its participation in the complement activation pathway, is a potential role of mannose-binding lectin (MBL) in HAE pathogenesis. Recently, a strong correlation between MBL levels and activity of the lectin pathway was described in both HAE patients and healthy controls [19].…”
Section: Introductionmentioning
confidence: 99%
“…The MASP-2 gene polymorphism exhibits a strong relationship with autoimmune diseases. Varga et al (2008) found that the lectin pathway might be activated in subjects with chlorine-esterase-inhibitor deficiency, which is associated with low MASP-2 and complement 4 levels. Thiel et al (2009) showed that human MASP-2 gene polymorphisms affect the protein folding of MASP-2 and binding efficiency of MASP-2 and mannan-binding lectin (MBL), in addition to autologous activation and serine protease activity.…”
Section: Introductionmentioning
confidence: 99%